Genome-wide characterization and sequence polymorphism analyses of cysteine-rich poly comb-like protein in Glycine max - Nisar, Tayyaba; Tahir, Muhammad Hammad Nadeem; Iqbal, Shahid; Sajjad, Muhammad; Nadeem, Muhammad Azhar; Qanmber, Ghulam; Baig, Ayesha; Khan, Zulqurnain; Zhao, Zhengyun; Geng, Zhide; Ur Rehman, Shoaib (Frontiers in Plant Science, 2022)
Cysteine-rich poly comb-like protein (CPP) is a member of cysteine-rich transcription factors that regulates plant growth and development. In present work, we characterized twelve CPP transcription factors encoding genes in soybean (Glycine max). Phylogenetic analyses classified CPP genes into six clades. Sequence logos analyses between G. max and G. soja amino acid residues exhibited high conservation. Presence of growth and stress related cis-acting element in the upstream regions of GmCPPs highlight their role in plant development and in tolerance against abiotic stress. Ka/Ks levels showed that GmCPPs experienced limited selection pressure with limited functional divergence arising from segmental or whole genome duplication events. By using PAN-genome of soybean, single nucleotide polymorphism was identified in GmCPP-6. To perform high throughput genotyping, a kompetitive allele specific PCR (KASP) marker was developed. Association analyses indicated GmCPP-6-T allele of GmCPP-6 (in exon region) associated with higher thousand seed weight under both water regimes (well-water and water-limited). Taken together, these results provide vital information to further decipher biological functions of CPP genes in soybean molecular breeding.